Association of the S267F Variant on NTCP Gene and Treatment Response to Pegylated Interferon in Patients with Chronic Hepatitis B: A Multicentre Study. Issue 1 (January 2018) - Thanapirom, Kessarin; Suksawatamnuay, Sirinporn; Sukeepaisarnjaroen, Wattana; Treeprasertsuk, Sombat; Tanwandee, Tawesak; Charatcharoenwitthaya, Phunchai; Thongsawat, Satawat; Leerapun, Apinya; Piratvisuth, Teerha; Boonsirichan, Rattana; Bunchorntavakul, Chalermrat; Pattanasirigool, Chaowalit; et al.
Background: Sodium taurocholate co-transporting polypeptide (NTCP) is a cell receptor for HBV. The S267F variant on the NTCP gene is inversely associated with the chronicity of HBV infection, progression to cirrhosis and hepatocellular carcinoma in East Asian populations. The aim of this study was to determine whether the S267F variant was associated with response to pegylated interferon (PEG-IFN) in patients with chronic HBV infection. Methods: A total of 257 patients with chronic HBV, treated with PEG-IFN for 48 weeks, were identified from 13 tertiary hospitals included in the hepatitis B database of the Thai Association for the Study of the Liver (THASL). Results: Of these, 202 patients were infected with HBV genotype C (84.9%); 146 patients were hepatitis B e antigen (HBeAg)-positive (56.8%). Genotypic frequencies of the S267F polymorphism were 85.2%, 14.8% and 0% for the GG, GA and AA genotypes, respectively. S267F GA was associated with sustained alanine aminotransferase (ALT) normalization (OR = 3.25, 95% CI 1.23, 8.61; P =0.02) in HBeAg-positive patients. Patients with S267F variant tended to have more virological response, sustained response with hepatitis B surface antigen (HBsAg) loss at 24 weeks following PEG-IFN treatment. There was no association between the S267F variant and improved patient outcomes in HBeAg-negative patients. Conclusions: The S267F variant on the NTCP gene is independently associated with sustained normalization of ALT following treatment with PEG-IFN in patients with HBV infection who are HBeAg-positive. The findings of this study provide additional support for the clinical significance of the S267F variant of NTCP beyond HBV entry.